PENGARUH DANA ALOKASI UMUM DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH (SURVEI PADA KABUPATEN/ KOTA SE-SULAWESI) - Ridwan , (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
The Influence of General Allocaation Fund and Regional Original Income on Regional Expenditure, a Survey in All Regency/ City in Sulawesi (supervised by Ridwan and Muslimin). The objective of this research is to analyze the influence of general allocation fund (DAU) and regional original income (PAD) on regional expenditure in all regency/ city in Sulawesi. The type of this research is descriptive and verificative method. To test the proposed hypothesis, this research employs multiple linear regression. The results from descriptive analysis indicates that financial performance using self-government ratio 2005 is 5.57% and in 2006 is 4.47%. This can be categorized that regional government is un-independent because the ratio is below 50%. Effectivity ratio 2005 is 90.86% (not effective) and 2006 is 108.02%. the results show that (1) simultaneously general allocation fund (DAU) and Regional Original Income (PAD) have a significant influence on regency/ city regional expenditure in Sulawesi (R2=0.951), (2) general allocation fund (DAU) partially has a significant influence on regional expenditure, (3) regional original income (PAD) has a significant influence on regional expenditure.